Literácia financeira de educadores: um estudo na rede pública do município de Sorocaba - Mota, Marcelo Nunes (2016)
It is understood that financial decisions, from the simplest to the most complex, are always present in people´s lives. In this sense, we can highlight the importance of foundations on the several resources used in purchasing, negotiation, applications, and other actions that require a minimum of financial insight. This set of knowledge is called financial education. Thus, this study aims to measure and determine the level of financial literacy of teachers in municipal primary and middle schools of Sorocaba, in its three dimensions (knowledge, behavior and attitude), with the use of studies about the extent of research on the theme, their metrics and their approaches. It highlights the importance of financial education during a person´s childhood and adolescence, and the formation of habits and principles as well, reinforcing the fact that one well informed educator can significantly contribute to future financial decisions of those individuals. A survey instrument, divided in three parts, was used for data collection. The first part was composed of demographic data about the teachers and their professional performance. The proposed scale for this part was categorical or metric (age and experience). The second part consisted of questions related to three dimensions: knowledge, behavior and attitude. These analyzed dimensions were proposed by Potrich et al (2015). The indicators (variables) of each dimension were adapted from Potrich’s instrument, and inspired by an OECD proposed survey for detecting levels of financial literacy as well. The third part of the questionnaire was based on S&P Klapper, Lusardi and Oudheesden (2014), when the teachers evaluated some investment-related situations and the value of money across the time. The proposed scale for this part of the questionnaire was nominal, being that each alternative showed a different behavior. Some of the factor analysis showed inconsistencies in the proposed dimensions. These proposed dimensions were stratified in three categories of clusters for each dimension, i.e. low, medium and high financial literacy. This study shows how that theme has been developed in the world and also in Brazil, as it turns evident that as far as there is a reduction of the barrier for financial inclusion, an awareness on the subject can be generated. Conclusions drawn from this work build an expectation to contribute to the evolution of the practice of financial education among the teachers of primary and secondary schools.